Mitigation of arsenic in broccoli through consumptive use of ground water and pond water as sources for irrigation. Issue 5 (16th April 2023) - Poddar, Ratneswar; Acharjee, Pravat Utpal; Bhattacharyya, Kallol; Patra, Sanmay Kumar
ABSTRACT: Arsenic (As) contamination in ground water is raising concerns due to indiscriminate irrigation for a large variety of crops. Therefore, it is a challenge to reduce As uptake in relation to safe human consumption either by reducing water supply or by improving water quality without major yield losses. The experiment was laid out in Randomized Block Design (RBD) replicated four times with five water management treatments viz . T1  = 100% shallow tube well (STW), T2  = 25% STW + 75% pond water (PW), T3  = 75% STW + 25% PW, T4  = 50% STW + 50% PW andT5  = 100% PW with broccoli (cv. Green Magic) as a test crop in an As-affected village of Ghetugachi, West Bengal, India. Plant and soil samples were collected during harvesting. The calculated hazard quotient (HQ) suggests that despite having higher yield, As content in broccoli under T1 is unfit for human consumption. T2 having a low HQ (0.564) and moderate crop water productivity (CWP) and irrigation water productivity (IWP) values (5.46 and 8.07, respectively) is marked as safest. T4 with moderately high HQ (0.776) and fairly high CWP and IWP (5.62 and 8.31, respectively) can be considered for areas having relatively less contamination.